Reproducibility of Measurements Obtained During Cardiopulmonary Exercise Testing in Individuals With Fatiguing Health Conditions: A Case Series. Issue 4 (October 2019) - Larson, Benjamin; Davenport, Todd E.; Stevens, Staci R.; Stevens, Jared; Van Ness, J. Mark; Snell, Christopher R.
Abstract : Purpose: Measurements obtained during maximal cardiopulmonary exercise testing (CPET) demonstrate high test–retest reliability, which indicates low error variance. However, measurements obtained from people with myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) may depart from typically observed high reproducibility, which could represent functionally relevant biological variability that is characteristic of the underlying pathophysiology. The purpose of this case series was to document individual experiences with test–retest variability in CPET measurements in individuals with ME/CFS compared with other fatiguing health conditions. Methods: In this case series, 6 women matched for age and body mass index underwent 2 maximal CPETs spaced 24 hours apart. Clients comprised 1 sedentary individual without fatigue, 1 active individual without fatigue, 1 individual with multiple sclerosis (MS), 1 individual diagnosed with HIV, 1 individual with ME/CFS and low maximal volume of oxygen consumed (VO2 max), and 1 high-functioning individual with ME/CFS and high VO2 max. Percent change in CPET measurements between tests was calculated for each client. Results: Nondisabled clients and clients with MS and HIV reproduced or improved in their volume of oxygen consumed (VO2 ), workload (WL), heart rate (HR), and minute ventilation (VE) at ventilatory anaerobic threshold (VAT) and at peak exercise (except peak WL and VE for the individual with HIV). Neither individual with ME/CFS reproduced VO2, WL, HR, or VE at VAT within literature estimates. Conclusions: Measurements during CPET for individual patients may relate to potential condition-specific deficits in cardiac, pulmonary, and metabolic functioning.